TINDAK TUTUR PENJUAL DAN PEMBELI DI PASAR TRADISIONAL KOTA TERPADU MANDIRI RASAU JAYA - Siti Azizah Ropiqoh; Agus Syahrani; Mellisa Jupitasari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe problem of this research are the types, components, function of the speech acts used by the sellers and buyers at the Traditional Market in the independent integrated city of Rasau Jaya, Kubu Raya Regency and the Implementation Plan to the Indonesian Language Learning. The aim of this research in general is to describe the speech acts used by the sellers and buyers in transactions at the traditional market in the Independent Integrated City (KTM) of Rasau Jaya. The main purposes are to describe the types, components, functions of the speech acts, and the plans for implementing to the Indonesian language learning. The method used in this research is descriptive method. The form of this research is qualitative. The research data collection was carried out by using the observation technique. The observation data will be collected by using recording tools and notes. Data analysis used is the criteria to determine the form of speech acts. The sources of data in this study are the sellers and buyers at the Traditional Market in the Independent Integrated City.Keywords: The Speech Acts, Sellers, Buyers, The Market KTM.